Hereditary microphthalmia in Texel lambs in Brazil - Gonçalves, Maiara Aline; Pereira, Paula Reis; da Cruz, Raquel Aparecida Sales; Panziera, Welden; de Andrade, Danilo Giorgi Abranches [UNESP]; de Oliveira-Filho, José Paes [UNESP]; Borges, Alexandre Secorun [UNESP]; Sonne, Luciana; Driemeier, David (Elsevier, 2018)
On a farm in southern Brazil, four lambs in a flock of 300 Texel sheep were born with bilateral blindness. They revealed bilateral occlusion of the eyelids and were unresponsive to external visual stimuli and were disoriented when walking. A post-mortem examination revealed bilateral occlusion of the eyelids and, microscopically, total or partial absence of the lens was observed. Blood samples from 20% of the herd (61/300) were sent for molecular analysis. The four affected lambs were homozygous (C/C) for a mutation (single-nucleotide polymorphism c.338G > C) in the PITX3 gene, and 26.2% (16/61) of the herd, including the two ewe and two ram parents, were heterozygous (G/C). Based on clinical, pathological and molecular analysis, it was possible to determine the existence of hereditary microphthalmia in Texel lambs associated with the c.338G > C SNP in the PITX3 gene for the first time in Brazil. The result of this study provides a warning to veterinarians and breeders, emphasizing the importance of considering this disease in the differential diagnosis of congenital diseases in the Brazilian Texel flock.
Keywords: Blindness; Congenital abnormalities; Eye diseases; Sheep; Texel